Geographical and historical background of the Hidatsa tribe (Journal of the College of Basic Education, 2022)
Undoubtedly, the issue of penetration into the subject of the American Indian tribes in the early days of the emergence of the US state government is one of the important topics for its close connection with important historical events that must be shed light on in order to know the extent to which these tribes are connected to their lands and areas of spread, and the Hidatsa tribe was among the American Indian tribes that It has its own language, beliefs, religious ceremonies and ways of obtaining its own food, and their social and cultural life has dominated the combative aspect, and this feature has become an associated part with it. The Hidatsa tribe engaged in trade after being attracted by the temptations of the profits of the fur trade. In Canada, as well as the tobacco trade that made it unique from the rest of the tribes of the northwest of the American continent, so we will try, through this research, to identify some of the social and economic aspects of the Hidatsa tribe.